Safety of baricitinib in vaccinated patients with severe and critical COVID-19 sub study of the randomised Bari-SolidAct trialResearch in context - Hans-Kittil Viermyr; Kristian Tonby; Erica Ponzi; Sophie Trouillet-Assant; Julien Poissy; José R. Arribas; Virginie Dyon-Tafani; Maude Bouscambert-Duchamp; Lambert Assoumou; Bente Halvorsen; Nuriye Basdag Tekin; Alpha Diallo; et al. (EBioMedicine)
Summary: Background: The Bari-SolidAct randomized controlled trial compared baricitinib with placebo in patients with severe COVID-19. A post hoc analysis revealed a higher incidence of serious adverse events (SAEs) among SARS-CoV-2-vaccinated participants who had received baricitinib. This sub-study aimed to investigate whether vaccination influences the safety profile of baricitinib in patients with severe COVID-19. Methods: Biobanked samples from 146 participants (55 vaccinated vs. 91 unvaccinated) were analysed longitudinally for inflammation markers, humoral responses, tissue viral loads, and plasma viral antigens on days 1, 3, and 8. High-dimensional analyses, including RNA sequencing and flow cytometry, were performed on available samples. Mediation analyses were used to assess relationships between SAEs, baseline-adjusted biomarkers, and treatment-vaccination status. Findings: Vaccinated participants were older, more frequently hospitalized, had more comorbidities, and exhibited higher nasopharyngeal viral loads. Baricitinib treatment did not affect antibody responses or viral clearance, but reduced markers of T-cell and monocyte activation compared to placebo (sCD25, sCD14, sCD163, sTIM-3). Age, baseline levels of plasma viral antigen, and several inflammatory markers, as well as IL-2, IL-6, Neopterin, CXCL16, sCD14, and suPAR on day 8 were associated with the occurrence of SAEs. However, mediation analyses of markers linked to SAEs, baricitinib treatment, or vaccination status did not reveal statistically significant interactions between vaccination status and SAEs. Interpretation: This sub-study did not identify any virus- or host-related biomarkers significantly associated with the interaction between SARS-CoV-2 vaccination status and the safety of baricitinib. However, caution should be exercised due to the moderate sample size. Funding: EU Horizon 2020 (grant number 101015736).